Diversity in Drought Traits among Commercial Southeastern US Peanut Cultivars - Mura Jyostna Devi; Thomas R. Sinclair (International Journal of Agronomy)
Commercial peanut cultivars in the USA are often grown under soil and environmental conditions resulting in intermittent periods of water deficit. Two plant traits have been identified that result in conservative use of water and allow sustained growth during drought: (1) restricted transpiration rate under high atmospheric vapor pressure deficit (VPD) and (2) earlier closure of stomata in the soil-drying cycle resulting in decreased daily transpiration rate. The objective of this study was to investigate whether there was diversity in these two putative traits for drought resistance among nine US commercial peanut cultivars. When the response to VPD was measured at an average temperature of 32∘C, eight of the nine cultivars expressed a restricted transpiration rate at high VPD. However, at 24∘C none of the cultivars exhibited a restriction of transpiration rate at high VPD. No differences were found among the nine cultivars in their response to soil drying.